2010
DOI: 10.1118/1.3431571
|View full text |Cite
|
Sign up to set email alerts
|

A time‐domain wavelet‐based approach for fluorescence diffuse optical tomography

Abstract: Purpose: In the context of fluorescence diffuse optical tomography, determining the optimal way to exploit the time-resolved information has been receiving much attention and different features of the time-resolved signals have been introduced. In this article, the authors revisit and generalize the notion of feature, considering the projection of the measurements onto some basis functions. This leads the authors to propose a novel approach based on the wavelet transform of the measurements. Methods: A compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Fast algorithms able to deal with very large datasets have been proposed for this modality [6,7], and it was observed that a limited number of patterns can be used in contrast to a large number of point-source illuminations. In parallel, the concept of data compression based on Fourier [8] or wavelet encoding [9,10] has been recently applied to CCD measurements acquired with point sources, in order to reduce the computational size of the problem. In this Letter, for the first time to our knowledge, we apply compression techniques to the measurements acquired with structured illuminations, implementing a simple approach that relies on the wavelet description of both source and detection spaces.…”
mentioning
confidence: 99%
“…Fast algorithms able to deal with very large datasets have been proposed for this modality [6,7], and it was observed that a limited number of patterns can be used in contrast to a large number of point-source illuminations. In parallel, the concept of data compression based on Fourier [8] or wavelet encoding [9,10] has been recently applied to CCD measurements acquired with point sources, in order to reduce the computational size of the problem. In this Letter, for the first time to our knowledge, we apply compression techniques to the measurements acquired with structured illuminations, implementing a simple approach that relies on the wavelet description of both source and detection spaces.…”
mentioning
confidence: 99%
“…The larger N max is (in practice the longer the integration time) the better the signal-to-noise ratio. The influence of N max is of particular interest since the reconstruction quality mainly depends on this parameter [24].…”
Section: Resultsmentioning
confidence: 99%
“…Here, the multiplicative constant, noted κ, is chosen so as to set the maximum number of detected photons N max to a prescribed value [24]:…”
Section: Noise Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Some related research on wavelet-based image reconstruction has been conducted. In [18], a time-resolved forward model and its projection onto wavelet basis functions have been implemented. Ducros et al apply compression techniques to the measurements acquired with structured illuminations [19].…”
Section: Image Reconstruction Based On the Wavelet Transformmentioning
confidence: 99%